Reinforced concrete cantilever retaining wall design consisting of two stage stem using Rao1 algorithm - Karabulut, Zehra Ertosun; Kurt, Zafer; Kalemci, Elifnur; Dede, Tayfun; Ikizler, Sabriye Banu (Emerald Group Publishing Ltd, 2025)
PurposeThis study aims to optimize the design of reinforced concrete retaining walls to achieve the lowest possible cost while maintaining structural stability and compliance with standards.Design/methodology/approachThe Rao1 algorithm was employed to optimize the design, considering seven independent variables related to geometry and four variables related to the reinforcement ratio. Geotechnical and structural analyses were performed using the Coulomb theory for static loads and the Mononobe-Okabe theory for dynamic loads. Cost calculations included concrete volume and reinforcement quantities across varying horizontal and vertical acceleration coefficients in four scenarios.FindingsThe optimization process revealed that the Rao1 algorithm consistently identified design variables near the lower regulatory limits, achieving the same cost across all scenarios. The results demonstrate that the Rao1 algorithm is an effective tool for optimizing the design of self-supporting reinforced concrete retaining walls, ensuring both cost efficiency and compliance with structural requirements.Originality/valueIn this study, the aim was to achieve an optimal, cost-effective design for retaining walls composed of a two-stage stem structure. Unlike conventional designs that utilize single-tier retaining walls, this study emphasizes the use of a two-stage stem configuration. It was noted that the Rao1 algorithm has not been previously applied to two-stage stem retaining walls in the literature. By applying the Rao1 algorithm, it was observed that a design meeting both minimum cost and required criteria was successfully achieved. Therefore, it was concluded that the Rao1 algorithm could be a valuable tool for retaining wall design. This study differs from other works in the literature both in terms of the two-stage stem-retaining wall design and the algorithm used.
Keywords: Best cost; Cantilever retaining wall structures; Metaheuristic algorithm; Optimal design; Rao1 algorithm